Cancer and the workplace: the employer perspective - Nobel, Jeremy (Medical Benefits, 2015)
Employers say that plans tend to make information readily available on care-related resources utilized and services billed for, but when it comes to actual outcomes, obtaining useful intelligence is often a challenge. Even among cancer practitioners, the definition of quality cancer care appears to differ, based on a myriad of varying expert opinions for different types of cancers.